Pengaruh Insentif Finansial Dan Non Finansial Terhadap Kepuasan Kerja Dan Kinerja Karyawan (Riset Empiris Pada Karyawan BRI Wilayah Kantor Cabang Sleman Yogyakarta) - Joko Wibowo (Universitas Muhammadiyah Yogyakarta, 2015)
A company's organization relies heavily on the management of human resources (HR), the employees who work for the company. The company always expects its employees can work well for the sake of the progress of the company, but only employees who have a high satisfaction will do its performance well with high loyalty. This research was conducted to determine the influence of financial and non financial incentives towards job satisfaction and employee performance on a BRI Branch Office of Sleman, Yogyakarta. The sample used as many as 200 employees BRI Branch Office of Sleman, Yogyakarta. The Data collected by the method of spreading the questionnaire directly to the respondents. Technique of data analysis in this study uses the SEM analysis (Structural Equation Modelling) that operated through AMOS. The results of this research are: financial incentives positive and significant effect on job satisfaction of employees; non financial incentives positive and significant effect on job satisfaction of employees; financial incentives positive and significant effect on performance of employees; non financial incentives positive and significant effect on performance of employees; and job satisfaction the positive and significant effect on the performance of employees.